Comparison of fasting and O G T T plasma glucose in the diagnosis of diabetes and pre-diabetes in Sri Lankan adults - Katulanda, G.; Mangaleshwaran, S.; Miriam, D.N.A.D.R.; Constantine, G.R.; Sheriff, R.; Mathew, R.R> (University of Colombo, 2011)
Fasting plasma glucose (FPG) and plasma glucose after an oral load of glucose (glucose tolerance test) are commonly used to diagnose diabetes and pre-diabetic categories like impaired fasting glucose (IFG) and impaired glucose tolerance (IGT)